The impact of the 2012 NZX listing rule change on board composition and company performance. Issue 4 (25th November 2020) - Boyle, Glenn; Hong, Sanghyun; Foley, Michael
Abstract : Purpose: This study aims to examine the impact of December 2012, New Zealand (NZ) stock exchange operator listing rule change that introduced compulsory disclosure about gender diversity on NZ boards. Design/methodology/approach: A quasi-natural experiment setting with a clearly identifiable exogenous event. Findings: The rate of growth in female-held directorships increased significantly after the introduction of the new rule, resulting in, by 2016, the average female board representation being more than double what it had been in 2012. However, this paper finds no relationship between this response and company performance. Research limitations/implications: This study cannot attribute causality to the observed jump in female directorships following the 2012 listing rule change due to the absence of a control group of firms not subject to this change. Practical implications: The results are consistent with an efficient director appointment process in NZ. Originality/value: Low-key regulatory changes can have a significant impact on company behaviour.